Transference kinetics of radioactive nuclide zirconium-95 in broadbean-soil system - ZHAO xi-yue; SHI jian-jun; WANG shou-xiang; CHEN chuan-qun (浙江大学学报. 农业与生命科学版)
The dynamics of transportation, accumulation, disappearance and distribution of 95Zr in the broadbean- soil system was studied by isotope-tracer technique, and the fitting equation was established by application of the closed two-compartment model and nonlinear regression method. The results showed: ①95Zr was transported in the system shortly after its addition into the surface layer of soil. 95Zr was absorbed mainly via root of broadbean and then redistributed among all parts of the broadbean plant. The concentration of 95Zr in the whole plant reached a maximum value, which was followed by a steady decrease. The concentration of 95Zr in root was much higher than in other parts of the plant. The concentrations of 95Zr in different parts of broadbean plant arranged in order was root > straw > husk > seed. ②Most of 95Zr detained in 6cm upon layer of the soil, and its concentration was single term exponential negative relation with depth of soil. ③The dynamics of 95Zr in broadbean-soil system could be described using multinomial exponential. ④Broadbean plant has the ability of enriching with 95Zr from soil to some extend.